A Systematic Review of Physical Activity, Sedentary Behavior, and Screen Time in Youth Aged 7–18 - Saudi, La; Lameky, Vernando Yanry (PT. Pubsains Nur Cendekia, 2025)
Background: The lack of physical activity, sedentary behavior, and screen time among children and adolescents has become a significant global health issue, contributing to an increased risk of non-communicable diseases, mental health disorders, and a decline in quality of life. Objective: To systematically review the existing literature on the trends of physical activity and sedentary behavior in children and adolescents, and their impact on non-communicable diseases. Method: This research utilized a systematic review method following the PRISMA guidelines to compile and evaluate 15 out of 2550 studies related to the relationship between physical activity, sedentary behavior, and screen time in children and adolescents. Literature searches were conducted in the PubMed, Scopus, and Google Scholar databases with specific inclusion criteria, and data analysis was performed comparatively to assess the quality and findings of the selected studies. Discussion: Increased sedentary time and decreased physical activity among children and adolescents may contribute to a higher risk of non-communicable diseases and mental health issues in the future. Therefore, interventions involving education, policies that support physical activity, and reduction of screen time are crucial to modify sedentary behavior and improve the quality of life for children and adolescents. Conclusion: Increasing physical activity and reducing sedentary time among children and adolescents are essential to prevent the risk of non-communicable diseases and support their future physical and mental health.